2019
DOI: 10.2337/dc19-0274
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and Cardiovascular Outcomes in Patients With Coronary Artery Disease and Prediabetes or Diabetes

Abstract: The aim of the current study is to determine the impact of elevated lipoprotein(a) [Lp(a)] on cardiovascular events (CVEs) in stable coronary artery disease (CAD) patients with different glucose metabolism status. RESEARCH DESIGN AND METHODS In this multicenter study, we consecutively enrolled 5,143 patients from March 2011 to February 2015. Patients were categorized according to status of glucose metabolism (diabetes mellitus [DM], pre-diabetes mellitus [pre-DM], and normal glucose regulation [NGR]) levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 31 publications
2
93
2
Order By: Relevance
“…Patients with CAD but without apparent glucose abnormalities were recommended to evaluate their glycemic state [36]. Prediabetes was associated with a worse prognosis in individuals with stable CAD only when combined with other cardiometabolic disorders [37][38][39]. Several previous studies demonstrated that the measurement of Fib provided incremental value to risk assessment in CAD patients with DM.…”
Section: Fib and Cardiovascular Outcomes In Patients With Coronary Armentioning
confidence: 99%
“…Patients with CAD but without apparent glucose abnormalities were recommended to evaluate their glycemic state [36]. Prediabetes was associated with a worse prognosis in individuals with stable CAD only when combined with other cardiometabolic disorders [37][38][39]. Several previous studies demonstrated that the measurement of Fib provided incremental value to risk assessment in CAD patients with DM.…”
Section: Fib and Cardiovascular Outcomes In Patients With Coronary Armentioning
confidence: 99%
“…Recently, our data proved that elevated Lp(a) levels were significantly associated with the risk of MACEs in patients with CAD combined with DM or pre-DM [18]. However, for patients with recent ACS who are treated with statins, Lp(a) concentration was not associated with MACEs [19].…”
Section: Inter-relationship Of Lp(a) Fib Levels and Cvesmentioning
confidence: 71%
“…As is well known, DM is a worldwide disease results in poor clinical outcomes, and is associated with large health-care costs. Nowadays, pre-DM has been attracted more attention because of its close association with increased cardiovascular risks [7][8][9][10][11]. In our previous studies conducted by Liu et al [9] and Jin et al [10], patients with pre-DM were more likely to have higher CVE risk when combined with other risk such as hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney function was measured as estimated glomerular filtration rate (eGFR) using Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation: 141 × min(SCr/κ, 1) α × max(SCr/κ, [29]. CAD was defined as the presence of coronary stenosis ≥ 50% at least one major artery segment assessed by two experienced physicians according to the results of CAG as mentioned in our previous studies [10]. The severity of coronary stenosis was assessed as Gensini Score (GS) system, which was defined as 1-point for < 25% stenosis, 2-point for 26-50% stenosis, 4-point for 51-75% stenosis, 8-point for 76-90% stenosis and 32-point for total occlusion.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation